Distinct Mechanisms Regulate Lck Spatial Organization in Activated T Cells - Kapoor-Kaushik, Natasha; Hinde, Elizabeth; Compeer, Ewoud B.; Yamamoto, Yui; Kraus, Felix; Yang, Zhengmin; Lou, Jieqiong; Pageon, Sophie V.; Tabarin, Thibault; Gaus, Katharina; Rossy, Jérémie (Frontiers in Immunology, 2016)
Phosphorylation of the T cell receptor (TCR) by the kinase Lck is the first detectable signaling event upon antigen engagement. The distribution of Lck within the plasma membrane, its conformational state, kinase activity, and protein–protein interactions all contribute to determine how efficiently Lck phosphorylates the engaged TCR. Here, we used cross-correlation raster image correlation spectroscopy and photoactivated localization microscopy to identify two mechanisms of Lck clustering: an intrinsic mechanism of Lck clustering induced by locking Lck in its open conformation and an extrinsic mechanism of clustering controlled by the phosphorylation of tyrosine 192, which regulates the affinity of Lck SH2 domain. Both mechanisms of clustering were differently affected by the absence of the kinase Zap70 or the adaptor Lat. We further observed that the adaptor TSAd bound to and promoted the diffusion of Lck when it is phosphorylated on tyrosine 192. Our data suggest that while Lck open conformation drives aggregation and clustering, the spatial organization of Lck is further controlled by signaling events downstream of TCR phosphorylation.